Pengelolaan Penerimaan Peserta Didik Baru Berbasis Iso 9001: 2008 Smk N 2 Surakarta - Amri, Ikhvan Assafa; , Prof. Dr. Sutama, M.Pd; , Dr. Suyatmini, M.Si (2016)
This study aims to 1) describe the promotion PPDB in SMK N 2 Surakarta, 2) describe the process of recruitment PPDB in SMK N 2 Surakarta, and 3) describe the follow up of the implementation of PPDB in SMK N 2 Surakarta. This type of research is qualitative research design fenomologi. Data collection techniques used were observation, interviews, and documentation. Data analysis technique used is model of the flow. The validity of the data is checked with a method of triangulation and the adequacy of the reference method. Results of the study were 1) this type of promotions that is used by SMK N 2 Surakarta are the making of the official website of SMK N 2 Surakarta, making of leaflets and pamphlets, conducting with several partners and reporting by the media on SMK Negeri 2 Surakarta, 2) providing the best services in the process PPDB is the result of the application of quality management ISO 9001: 2008 that sustainable, and SMK N 2 Surakarta also collaborates with other stakeholders to support the professionalism of the school, 3) follow-up activities of PPDB SMK N 2 Surakarta as the implementation of school orientation that reflects the introduction of physical and social environment, and also the establishment of student character. Grading objectively resulting grouping students according to their interests, abilities, and intelligence. All kinds of activities that aim to support the creation of effective teaching and learning processes in the environment SMK N 2 Surakarta. Keyword: promotion, recruitment, orientation